2013
DOI: 10.1109/tuffc.2013.2751
|View full text |Cite
|
Sign up to set email alerts
|

Temperature rise in tissue ablation using multi-frequency ultrasound

Abstract: High-intensity focused ultrasound (HIFU) is becoming an increasingly important noninvasive surgical tool, despite the challenges in temperature rise control and unwanted heating problems. In this study, experiments and simulations on tissue ablation effectiveness were performed using multi-frequency HIFU with frequency differences of more than 500 kHz (center frequencies are 950 kHz, 1.5 MHz, and 3.3 MHz). In the experiments, the temperature was recorded as chicken breast tissue was heated by single-frequency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
0
35
1
Order By: Relevance
“…At 30 W or more, single 1.1 MHz HIFU increased the temperature significantly, while 5 MHz HIFU showed no obvious effects on temperature rise even at 60 W. However, dual-frequency HIFU co-irradiation significantly increased the temperature of the focal region in the phantom in the lower power range (10 and 20 W) compared with single 1.1 MHz HIFU. It might be that dual-frequency HIFU irradiation can produce more cavitation bubbles and increase the energy absorption of the phantom [34,38]. At the same time, a large number of inertial cavitation can also increase heat production [34], significantly increasing the temperature at the low power of dual-frequency HIFU.…”
Section: Evaluation Of Thermal and Cavitation Effects In The Biomimetic Phantommentioning
confidence: 99%
See 1 more Smart Citation
“…At 30 W or more, single 1.1 MHz HIFU increased the temperature significantly, while 5 MHz HIFU showed no obvious effects on temperature rise even at 60 W. However, dual-frequency HIFU co-irradiation significantly increased the temperature of the focal region in the phantom in the lower power range (10 and 20 W) compared with single 1.1 MHz HIFU. It might be that dual-frequency HIFU irradiation can produce more cavitation bubbles and increase the energy absorption of the phantom [34,38]. At the same time, a large number of inertial cavitation can also increase heat production [34], significantly increasing the temperature at the low power of dual-frequency HIFU.…”
Section: Evaluation Of Thermal and Cavitation Effects In The Biomimetic Phantommentioning
confidence: 99%
“…More cavitation activities were also confirmed at the dual-frequency excitation, which may improve the performance of HIFU ablation [33]. In addition, studies have shown that tissue ablation using dual-frequency HIFU yield a higher temperature and a higher temperature rise rate compared with ablation using single-frequency HIFU under the same exposure power and time [34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to imaging, ultrasound therapy can benefit from multifrequency transducers. Recent works on multifrequency tissue ablation found that temperature rise rate and saturated temperature due to bioheating could be higher by using multifrequency ultrasound rather than the conventional single frequency one, which is likely attributed to the enhanced cavitation in tissue ablation using multifrequency ultrasound [21,22]. Similarly, thrombolysis using dual frequency ultrasound showed enhanced lytic rate over the conventional single frequency ultrasound [23].…”
Section: Multi-frequency Transducersmentioning
confidence: 99%
“…Focusing ultrasonic waves has multiple applications in various fields, such as non-destructive testing in industrial scenarios 1 , biomedical imaging of different kind of tissues 2 , or thermal ablation of tumours through High Intensity Focused Ultrasound (HIFU) 3 5 . Different techniques have been devised in the literature to achieve multiple acoustic foci.…”
Section: Introductionmentioning
confidence: 99%